ANALISIS KELAYAKAN PENGEMBANGAN WISATA BUDAYA DI DUSUN TUTUP NGISOR DALAM PERSPEKTIF PARIWISATA BERKELANJUTAN - , AFIFATUL KARIMAH; , Prof. Dr. Marsono, S. U. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Cultural tourism is one of the trends which is developing among others tourism. Touristsâ motivations to know about culture, custom, tradition and others local art are chances to the development of the attractiveness of alternative tourism which offers activities that are familiar with socio-cultural sense. One of the attractiveness of tourism which can be developed is local culture that can be arranged in a tourism village. The potency belonged to Tutup Ngisor village is the same compared to others tourism village that have existed in Magelang Regency. The location is strategic since it is between Borobudur Temple and Ketep Pass. Many tourists visit to Tutup Ngisor village when a performance is hold. The concept applied in this research is appropriateness concept which consists of physical aspect, trade and marketing aspect, organizational and managable aspect, economical aspect and external aspect ( Tourism Center Learning UGM, 2012). To actualize sustainable tourism, the appropriateness concept must be appropriate to sustainable tourism parameter consisting of economical, social, and physical environment (Swarbrooke, 1999). This research results that Tutup Ngisor village is appropriate to be developed as an sustainable cultural tourism. Based on the environmental aspect, Tutup Ngisor village is able to take care of its environment and anticipate negative effects caused by tourism activities. Based on socio-cultural, Tutup Ngisor village is valued to be able to preserve the originality of the cultural-art especially there is Padepokan Tjipta Boedaya Art. Based on economical aspect, the tourism activities can create field works for the society, so that it can increase the prosperity of the society. The recommendations of the development of Tutup Ngisor village as cultural agro-tourism is creating various of tourism products which can be enjoyed by the visitors out of the performance time, increasing the societyâs preparation to actualize Tutup Ngisor village as cultural argo-tourism, and informating and educating the society to anticipate bad effects appeared by tourism activities.